Does handgrip strength effect pulmonary function in healthy children? - Muhammet Hakan Mayda; Serhat Erail (ROL Spor Bilimleri Dergisi, 2023)
The present study examined the relationship between hand grip strength and pulmonary functions of healthy children and the aim was to use regression model and hand grip strength as a practical tool to predict pulmonary functions. The study was designed as cross-sectional and analytical. A total of 755 healthy children (age= 9.38±0.48) participated in the study voluntarily. Hand grip strength and respiratory function tests were applied to the children. In statistical analysis, Pearson correlation and linear regression model were used. A significant correlation was found between right and left hand grip strength and FVC, FEV1 and PEF (p<0.05). In addition, while the left hand grip strength had a significant effect on the lung function parameters FVC, FEV and PEF (p<0.05), it was found that the right hand grip strength was not a significant predictor of the parameters (p> 0.05). As a result, it was concluded that there are correlations between HGS and functional respiratory parameters in children, just as in adults and patient groups. In order to analyse the correlations between HGS and respiratory functions more clearly, it is recommended to examine important factors such as different age, activity levels and gender together in new studies.